Carbon Nanozymes: Enzymatic Properties, Catalytic Mechanism, and Applications. Issue 30 (7th May 2018) - Sun, Hanjun; Zhou, Ya; Ren, Jinsong; Qu, Xiaogang
Abstract: Nanozymes have advantages over natural enzymes, such as facile production on large scale, long storage time, low costs, and high stability in harsh environments. Carbon nanomaterials (CNMs), including fullerenes, carbon nanotubes, graphene, carbon quantum dots, and graphene quantum dots, have become a star family in materials science. As a new class of nanozymes, the catalytic activity of CNMs and their hybrids has been extensively reported. In this Minireview, recent progress of CNMs based artificial enzymes, focusing on those with peroxidase‐like activity, has been summarized. The enzymatic properties, catalytic mechanisms, and novel applications of CNM nanozymes in sensing, therapy, and environmental engineering are discussed in detail. Additionally, we also highlight the remaining challenges and unsolved problems. With the fast development of bionanotechnology, the unique enzymatic properties and advantages of CNM nanozymes have received much attention and will continue to be an active and challenging field for the years to come. Abstract : Artificial peroxidases : Recent progress on carbon‐nanomaterial‐based artificial enzymes, including their enzymatic properties, catalytic mechanisms, and novel applications, is presented. The unique properties and advantages of carbon nanozymes have been successfully used in sensing, wound healing, therapy, and environmental engineering.